Transport properties of mixed matrix membranes encompassing zeolitic imidazolate framework 8 (ZIF-8) nanofiller and 6FDA-durene polymer: Optimization of process variables for the separation of CO2from CH4 - Jusoh, N. (Elsevier Ltd, 2017)
In this work, the incorporation of ZIF-8 nanofiller for the improvement of the transport properties of 6FDA-durene membrane in CO2/CH4separation is investigated. Central composite design (CCD) coupled with response surface methodology (RSM) were utilized for the optimization of the separation process variables over ZIF-8/6FDA-durene MMM in CO2/CH4separation. Three models correlating the independent parameters including, pressure (3.5–12.5 bar), temperature (30–50 °C) and CO2concentration (10–90 vol) with the responses including, CO2permeability, CH4permeability and CO2/CH4selectivity were developed based on the experimental data. The optimum parameters for achieving the highest separation performance were obtained at pressure of 4.76 bar, temperature of 30 °C and CO2concentration of 90 vol, which resulted in CO2permeability of 687.20 Barrer, CH4permeability of 71.03 Barrer and CO2/CH4selectivity of 8.92. The deviation of the corresponding experimental data was found to be in an acceptable range, confirming the suitability of RSM for predicting the membrane performance and consequently optimizing the separation process variables. © 2017 Elsevier Ltd